Perspective of the Accountant's Code of Ethics on Weton Market Characteristics According to Cultural Beliefs - Habsyah Fitri Aryani; Siti Nur Hanifa; Muhammad Aras Prabowo (Trescode Green Organization, 2025)
This research aims to find out and understand the accounting code of ethics. The accounting code of ethics is a set of principles and standards designed to serve as guidelines for accountants to behave professionally and responsibly in carrying out their duties. The accounting code of ethics consists of five accounting principles. including objectivity, integrity, confidentiality and professional behavior, competence and professional prudence. These five basic principles can be internalized into the character of market days according to Javanese cultural beliefs. The market day consists of five days, namely legi, pahing, pon, wage, and kliwon. The five market days have different characteristics. The characteristics of each market day can be used as role models for an accountant in carrying out professional duties and responsibilities. This research uses a literature review study with an explanation of each basic principle of accounting professional ethics which is then internalized into the weton character of Javanese cultural market days.